Mass Movement Using the Bingham Fluid Model and the Voellmy Fluid Friction Model. (Case Study of Songan Village, Kintamani, Bali) - Widjaja B; Prakoso J S (Bandar Lampung University (UBL), 2017)
Indonesia is located on the Ring of Fire of Pacific Rims. This condition makes Indonesia at risk of geological disaster. One possible occurrence is mudflow. On February 10, 2017, mudflow occurred in Songan Village, Kintamani, Bali, which destroyed 6 houses and killed 13 people. Further study is needed to predict this type of occurrence. This study aims to identify the characteristics of the soil at the deposition area of mudflow and verify the duration, flow depth, and velocity of mudflow. To achieve these objectives, a rheological study is conducted using the Bingham fluid model and the Voellmy fluid friction model in Flo-2D and Rapid Mass Movement Simulation (RAMMS), respectively; the simulation results of both models are compared. From the results of the programsimulations, RAMMS’ results are found to exhibit a higher velocity of mass movements than that of Flo-2D’s results. From the results of this analysis, small viscosity is observed to result in small flow depth and high velocity of mass movements. Keywords—Mudflow, Bingham, Voellmy, Flo-2D, RAMMS.